FACTORS AFFECTING THE SELECTION OF THIRD-PARTY LOGISTICS SERVICE PROVIDERS IN THE EDIBLE OIL INDUSTRY OF KARACHI - SALMAN AHMED; DR. MUHAMMAD ASIM; SALMAN MANZOOR (CenRaPS Journal of Social Sciences, 2020)
Purpose: Logistics plays an important role in integrating the supply chain of industries. But given the volatility and dynamic nature of supply chain management as a field, the factors that need to be considered when choosing a 3PL can vary based on geographic location, type of industry, nature of the product and so on. Therefore, this study aims to identify which factors impact 3PL Service Provider selection the most in the edible oil industry specifically based in Karachi. Design: The study describes and the theory of core competencies and how these competencies are used in the selection process of 3PL Service Providers. A survey was carried out through questionnaires to determine which competencies are best suited to choosing a 3PL Service Provider in the edible oil industry. Findings: The findings showed the Selection of 3PL Provider was most significantly impacted by two of the five variables Cost of Service and Operational Performance. Financial Performance showed a weak relationship while the last two variables were proven to have little or no relationship with the independent variable. Originality and Value: The study will help the supply chain professionals of the edible oil companies focus on certain factors while outsourcing their work most importantly selecting a 3PL service provider.